2021
DOI: 10.1007/s00468-021-02092-0
|View full text |Cite
|
Sign up to set email alerts
|

Tree growth as affected by stem and crown structure

Abstract: Key message Prediction of tree growth based on size or mass as proposed by the Metabolic Scaling Theory is an over-simplification and can be significantly improved by consideration of stem and crown morphology. Tree growth and metabolic scaling theory, as well as corresponding growth equations, use tree volume or mass as predictors for growth. However, this may be an over-simplification, as the future growth of a tree may, in addition to volume or mass, also depend on its past devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(12 citation statements)
references
References 41 publications
0
12
0
Order By: Relevance
“…One approach that may have promise would initially involve derivation of a model that would describe size effects on individual tree growth rates for a species when trees were open-grown and not subject to competitive interactions with neighbors. A number of model systems have been based on that approach (e.g., Pommerening and Maleki 2014;Lamonica et al 2020;Bhandari et al 2021;Pretzsch 2021). Once that was determined, competition indices that describe above-and below-ground competitive processes separately might then be added to the system to attempt to quantify symmetric and asymmetric processes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…One approach that may have promise would initially involve derivation of a model that would describe size effects on individual tree growth rates for a species when trees were open-grown and not subject to competitive interactions with neighbors. A number of model systems have been based on that approach (e.g., Pommerening and Maleki 2014;Lamonica et al 2020;Bhandari et al 2021;Pretzsch 2021). Once that was determined, competition indices that describe above-and below-ground competitive processes separately might then be added to the system to attempt to quantify symmetric and asymmetric processes.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies of the effects of competitive process on forest growth behavior have been based on this type of testing (Nystrom and Kexi 1997;Gourlet-Fleury and Houllier 2000;Lessard et al 2001;Mabvurira and Miina 2002;Mailly et al 2003;Monty et al 2008;Pérot et al 2010;Pedersen et al 2012;Carr et al 2020;Barros de Oliveira et al 2021). However, of recent times it has become common to use 'Akaike's Information Criterion' (AIC) (and allied criteria) to suggest which of a number of possible models is the most appropriate when fitted to a particular data set; a number of studies of competitive processes have used this method (Miina and Pukkala 2002;Papaik and Canham 2006;Yang et al 2009;Pretzsch 2021). Some studies have used both methods (Pommerening and Maleki 2014;Cordonnier and Kunstler 2015;Kahriman et al 2018;Acquah and Marshall 2020;Bhandari et al 2021) or, indeed, have used other methods altogether (Verzelen et al 2006;Kuehne et al 2019).…”
Section: Fitting and Testing The Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study, we modeled tree growth and drought responses in dependence on the basal area of each tree. However, it has recently been shown that the crown structure is also an important growth determinant [143]. Thus, if crown morphology had been surveyed more than once, it also could have been included in our modeling approach.…”
Section: Methodological Considerationsmentioning
confidence: 99%
“…These, together with the physiological capabilities of the species concerned, will determine the size the tree might reach by any particular age. That size is then the second factor that determines how fast it may grow subsequently (Pretzsch 2021a); this reflects the amount of living tissue it contains to undertake growth processes (Weiskittel et al 2011, Chap 12). The third factor is the availability to the tree of the resources it requires for growth, light, carbon dioxide, water and nutrients.…”
Section: Introductionmentioning
confidence: 99%